A case of cervicomedullary junction compression - Ashok Gupta; Priyanshu Mathur; Manish Sharma; Vimesh Parmar (Wolters Kluwer Medknow Publications, 2017)
The C-V junction is a transition site between mobile cranium and relatively rigid spinal column. It is also the site of the medullo-spinal junction. CV anomalies are defects of development, not necessarily congenital and may not manifest at birth. These anomalies can lead to spinal cord compression, cranial nerve compression, vertebral artery compression and obstructive hydrocephalus. Delay in diagnosis can result in irreparable damage to spinal cord and can lead to permanent disability or even death. MRI of cervical spine helps us in diagnosis of CVJ anomalies and is the investigation of choice. We are presenting a case of 12 years old female child presented with history of progressive weakness of both upper and lower limbs, difficulty in walking and history of frequent falls with transient loss of consciousness for last 4 years. She was found to have CVJ anomalies on MRI cervical spine but had already developed permanent disability due to atrophy of spinal cord due to prolonged compression.